1999
DOI: 10.1021/la990645g
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary Ammonium Bromide Surfactant Oligomers in Aqueous Solution:  Self-Association and Microstructure

Abstract: Surfactant oligomers are made up of x (g2) amphiphilic moieties connected at the level of, or close to, the headgroups by spacer group(s). This paper examines the effect of the degree of oligomerization x on the self-assembling of cationic surfactant oligomers at interfaces and in the bulk. The quaternary ammonium bromide surfactant oligomers investigated are made up of dodecyldimethyl-and dodecylmethylammonium bromide moieties connected by short polymethylene spacers -(CH2)s-(of carbon number s). The properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
168
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(186 citation statements)
references
References 40 publications
13
168
0
3
Order By: Relevance
“…• (C 12 ), for two series of oligomeric surfactants (34). These values were calculated with the available cmc and ionization data, using the appropriate equation (35).…”
Section: Aqueous Dimeric Surfactant Solutions At Concentrations Bmentioning
confidence: 99%
See 1 more Smart Citation
“…• (C 12 ), for two series of oligomeric surfactants (34). These values were calculated with the available cmc and ionization data, using the appropriate equation (35).…”
Section: Aqueous Dimeric Surfactant Solutions At Concentrations Bmentioning
confidence: 99%
“…The adsorption isotherms of dimeric 12-s-12 (50-52), trimeric 12-s-12-s-12 (34,53), and tetrameric 12-3-12-4-12-3-12 cationic surfactants on macroporous amorphous silica showed that the adsorption involves two steps, as for conventional surfactants (34). The first step occurs at very low concentration and corresponds to a binding of individual dimeric surfactants to charged sites on the silica surface by an ion-exchange mechanism.…”
Section: Solid-solution Interfacementioning
confidence: 99%
“…[4]; the result is K 1 = 359 and 497 M −1 for spherical and angular particles, respectively. Since in our experiments c 1s can be ≥3 × 10 −3 M (see Fig.…”
Section: Figmentioning
confidence: 93%
“…Various techniques have been applied to measure the depletion effect: colorimetric titration methods (1)(2)(3)(4), static (5)(6)(7) and dynamic (8) surface-tension experiments, UV spectroscopy (9)(10)(11), fluorescence (12), and high-pressure liquid chromatography (13) [see also studies cited in Ref. (2)].…”
Section: Introductionmentioning
confidence: 99%
“…Within this series, cationic gemini surfactants have been most widely investigated due to their favorable physicochemical properties [1,2]. However, most of the published results concentrate on dimeric quaternary ammonium salts [2], and occasionally on trimeric and tetrameric surfactants [8][9][10] and multi-armed oligomeric cationic surfactants that have 4 or 6 quaternary ammonium sites [11]. To the best of our knowledge, however, the quaternary ammonium geminis that possess four hydrophobic tails, each two of which are attached to one of the two hydrophilic heads, have been less well documented [12,13].…”
Section: Introductionmentioning
confidence: 99%